Las élites palestinas de Jerusalén - Blufstein, Ariel (2000)
The aim of this paper is to offer an approach to the world of the Palestinian elites in Jerusalem. In order to achieve this, I am focused on the Nashashibis and Husaynis, and on the relationship between these and the foreign powers that have governed their land. As a preliminary step, I offer an analysis on the elites theory, first of all by referring to its main scholars, Mosca and Pareto, and eventually by introducing the analysis made by several scholars such as Bottomore, Schumpeter and Mills, just to mention a few specialist in the field. (Párrafo extraído del texto a modo de resumen)